PENANGGANAN GANGGUAN FREKUENSI RADIO RADAR CUACA BMKG WILAYAH III DENPASAR PADA PITA FREKUENSI 5 GHz - Bayu Sanjaya, Ketut Bagus; Oka Widyantara, I Made; Djuni Hartawan, I G A Komang (Jurnal SPEKTRUM, 2023)
The existence of a radio frequency spectrum is regulated by the state as stated in Government Regulation number 53 of 2000, which is a limited natural resource that has strategic value in the operation of telecommunications. And the utilization of the radio frequency spectrum as a natural resource needs to be carried out in an orderly, efficient and appropriate manner so as not to cause harmful interference. Denpasar Class I Radio Frequency Spectrum Monitoring Center (Balmon Denpasar) as one of the UPT (Technical Service Units) of the Directorate General of SDDPI has the task of carrying out supervision and control in the field of radio frequency spectrum use in the Bali region. This study aims to be able to carry out supervision and observation of the radio frequency spectrum through observation (Ocupansy). Seeing the scope of the existing problems, this practical work report will provide the following problem boundaries: Observation of the occupation of the radio frequency spectrum through observation, measurement of technical parameters and law enforcement. There are complaints of disturbances on the radio frequency 5625 MHz for weather radar by the Meteorology, Climatology and Geophysics Agency (BMKG) Region III Denpasar caused by the use of the 5 GHz band frequency by ISPs using wireless LAN.